Naturally Occurring Compounds as Potential Inhibitors of Epidermal Growth Factor Receptors (EGFRs) - Oktavia, Listiana; Fuad, Asrul M.; Senjaya, Seni Kurnia; Yuliyawati, Yuliawati (Combinatorial Chemistry & High Throughput Screening, 2023)
The Epidermal Growth Factor Receptor (EGFR) activation appears essential in tumor growth and progression. Targeting EGFR signaling pathway has become an exciting area in cancer therapy. Synthetic chemotherapy drugs have been used to inhibit some EGFR signaling in various cancer cells. The use of naturally occurring compounds as EGFR inhibitors is an attractive area for research due to the urgent need to combat resistance over current EGFR inhibitors. In this review, we first summarize the schematic role of EGFR in cancer and the current EGFR inhibitor used, its advantage, and disadvantage. Next, we discuss the natural products that have been reported as the source of EGFR inhibitors. The discussion covers the natural products which where majorly reported from the year 2005-2020. A total of 21 groups of natural compounds and their derivatives were reported to have the potential to inhibit EGFR signaling pathways. We then discuss the advanced technologies and approaches that rapidly discover EGFR inhibitor-based natural products. Hopefully, this literature review could increase the excitement of finding an effective EGFR pathway inhibitor from natural products.
Keywords: chemotherapy